The International Monetary Fond as a creator of the global financial system - Violeta Spaseska Kitanovic; Saso Kozuharov (UTMS Journal of Economics, 2012)
IMF and World Bank were created after the Second World War as a result of monetary and fiscal Conference of the United Nations (UN) in the Bretton Wood, New Hampshire in July 1944. This conference was part of the efforts to finance the construction of Europe which was destroyed in the Second World War, and to protect the world from further economic depressions. The decision that was reached at Breton Wood was influenced by the global economic depression which had affected the world in the yearly thierties.That was the biggest crisis that with with the capitalism confronted. The unemployment grew with tremendous speed and for a short time period almost one quarter quarter of the U.S. working-age population was unemployed. English economist John Maynard Keynes claimed that the cause of economic recession is insufficient demand.
Keywords: F33; F35; 330; International Monetary Fond; World Bank; regulation; economic recession